Development of Quantum Physics Laboratory Based on Immersive Virtual Reality - Mufit, Fatni; Dhanil, Muhammad; Hendriyani, Yeka (Society of Visual Informatics, 2025)
This study aims to develop a VR-based quantum physics laboratory to visualize quantum physics phenomena and support more interactive and efficient learning. The research method follows the stages of needs analysis, design and development, and implementation. The needs analysis stage involved 97 students to gather information about the challenges in quantum physics learning.The needs analysis results showed that quantum physics was a difficult subject to understand due to its abstract nature, and there was a need for media that could help students understand the material through simulations and experiments in a virtual environment. The design and development stage produced scenarios and storyboards encompassing all the necessary elements for VR implementation. During the implementation stage, the design was realized in the form of a VR laboratory presenting various quantum physics experiments, including black body radiation, the Compton effect, the photoelectric effect, and X-ray production. The results of the implementation of the use of VR through validity testing and practicality tests obtained a score of 0.92 in the valid category and 92.25% in the very practical category. This research contributes to supporting the availability of quantum physics experimental equipment in schools and makes it easier for students to understand abstract quantum physics concepts through interesting virtual interactivity. The VR-based quantum physics laboratory was successfully developed as an innovative solution for quantum physics learning. Future research suggests that VR can be developed for other learning areas and that further studies explore the effects of VR on skills and health.